Sex Disparities in Diagnostic Evaluation and Revascularization in Patients With Acute Myocardial Infarction—A 15‐Year Nationwide Study - Muddasir Ashraf; M. Fuad Jan; Tanvir. K Bajwa; Ryan Carnahan; Viviana Zlochiver; Suhail Q. Allaqaband (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Although sex disparities in the diagnostic evaluation and revascularization of patients with acute myocardial infarction are well documented, no study has evaluated longitudinal trends in these disparities. Methods and Results Using the National Inpatient Sample from 2005 to 2019, 9 259 932 patients with acute myocardial infarction were identified. We divided 15 years into five 3‐year periods. The primary objective was to evaluate sex‐based trends in the use of diagnostic angiography, percutaneous coronary intervention, and coronary artery bypass graft (CABG) among patients with non–ST‐segment–elevation myocardial infarction and ST‐segment–elevation myocardial infarction (STEMI) over 15 years. The secondary objective was to evaluate sex disparities in mortality, length of stay, and cost. For non–ST‐segment–elevation myocardial infarction, we saw a small reduction in sex disparity in the use of all diagnostic angiography in period 5 versus period 1 (4% versus 5.3%; P<0.01), no change in sex disparity in percutaneous coronary intervention use in period 5 versus period 1 (5.6% versus 5%; P=0.16), and a widening sex disparity in CABG in period 5 versus period 1 (5.4% versus 4.4%; P<0.01). However, we noted decreasing sex disparities in the use of diagnostic angiography, percutaneous coronary intervention, and CABG for ST‐segment–elevation myocardial infarction in mostly all periods compared with period 1 (P<0.05, all comparisons), but differences still existed in period 5. Risk‐adjusted in‐hospital mortality was higher after CABG for non–ST‐segment–elevation myocardial infarction and after percutaneous coronary intervention and CABG for ST‐segment–elevation myocardial infarction in women than men. Conclusions Despite variable trends in sex disparities in diagnostic and revascularization procedures for acute myocardial infarction, disparities still exist.